Assessing and monitoring injury risk factors in young gymnasts - Williams, E. R.; Lloyd, R. S.; Moeskops, S.; Pedley, J. S. (Strength and Conditioning Journal, 2025)
Talented young gymnasts often specialize at a very young age and can engage in very high volumes of high-intensity training. However, sampling gymnastics is beneficial for the development of young athletes in all sports as it develops coordination, strength, and balance. The repetitive nature of gymnastics practice, coupled with high training loads, can interact with natural processes of growth and maturation and potentially elevate the probability of injury if consideration is not given to monitoring risk factors and modifying training accordingly. Therefore, a systematic approach to identifying injury risk factors in youth gymnasts is required. In the absence of direct evidence in young gymnasts, a testing battery based on best available evidence from youth sports is recommended to assist gymnastics coaches to monitor fluctuations in risk as their gymnasts grow and mature.